Strategi Pemasaran Beras Berdasarkan Analisis Tahap Business Life Cycle dan Analytical Hierarchy Process di PT Komoditi Tani Indonesia - Pramesthi, Fatima Azrina; Yektiningsih, Endang; Fitriana, Nisa Hafi Idhoh (JURNAL AGRICA, 2025)
Marketing strategy is a way for companies to win a sustainable competitive advantage for both companies that produce goods or services. Every company will experience a business life cycle, this makes the company have to develop a marketing strategy according to the stage that is being experienced. This study aims to analyze the business position of PT Komoditi Tani Indonesia based on the stage of the business life cycle of rice produced and formulate the right marketing strategy. The sampling method used purposive sampling with a total of 6 expert respondents. The analytical method used is the Dickinson method and analytical hierarchy process using expert choice 11 software. It was shown by the results that in the business life cycle, the current business position of PT Komoditi Tani Indonesia is still in the introduction stage (start-up) with the characteristics of negative operational cash flow, negative investment cash flow, and positive funding cash flow. Then the results of the analytical hierarchy process of rice marketing strategies produce a priority order of marketing strategies based on the start-up stage, which includes developing product designs, participating in relevant events, product discounts, improving quality, bundling prices, collaborating with influencers, selling in supermarkets and selling in e-commerce. Companies need to develop marketing strategies that are in accordance with the stage of the business life cycle that is being undertaken, especially at the start-up stage to build brand awareness and attract consumers.